Evaluating regional tourism competitiveness through the competitiveness monitor framework: A spatial and policy-based approach to place branding - Syafirah, Nurul Mutia; Mujahid, Laode Muhammad Asfan (The Journal of City: Branding and Authenticity, 2025)
Background: Cilacap Regency, the largest in Central Java, has great potential for tourism development due to its diverse natural and demographic characteristics. However, tourism has not yet become a leading sector in regional revenue. To optimize development, it is essential to assess both internal and external subsystems of the tourism sector and measure its competitiveness against national standards. Methods: This study used a combination of qualitative and quantitative descriptive methods. The Competitiveness Monitor framework with eight indicators was applied to evaluate tourism competitiveness. Spatial analysis, including identity and union overlays, was used to analyze geographical factors. Data were collected through field observations, secondary data from Regional Government Organizations (OPD), and online sources, which were then mapped and interpreted. Findings: The results of this study show that Cilacap Regency is located in a coastal area with gentle slopes that dominate 58.76% of the total area. Because of these natural factors, many natural attractions are found in this regency coupled with the regency capital being right on the coast which makes tourism businesses develop a lot in this area. In addition to natural factors, Cilacap Regency Tourism is also supported by demographic, socio-cultural, technology use, economic, and political factors that discuss tourism policy. Through measurements using the Competitiveness Monitor, of the eight indicators, one indicator is in the improvement stage, namely EI, six of which are in the developing stage, namely HTI, PCI, IDI, TAI, HRI, and SDI. And one indicator is still in the undeveloped stage, namely OI. Conclusion: With targeted strategies, Cilacap can enhance its competitiveness and move toward becoming a prominent tourism destination on a national scale. Novelty/Originality of this article: It uniquely maps the relationship between geographic, demographic, economic, and infrastructural variables, presenting a detailed, data-driven roadmap for future tourism development in a region where tourism is not yet a primary economic sector.